2019
DOI: 10.1111/hex.12898
|View full text |Cite
|
Sign up to set email alerts
|

Supporting self‐management after traumatic brain injury: Codesign and evaluation of a new intervention across a trauma pathway

Abstract: Background Supported self‐management (SSM) is a recognized approach for people with long‐term conditions but, despite the prevalence of unmet needs, little is known about its role for people with traumatic brain injury (TBI). Objectives To codesign an SSM intervention with people with TBI and evaluate feasibility of implementation through multidisciplinary staff across a trauma pathway. Setting and participants People who had previously been admitted to a Major Trauma Centre following TBI and family members pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…However, we acknowledge that this response may ultimately be inadequate and the flexibility, although clearly an ideal and desirable feature to fit a wide range of situations [14], may be difficult to balance with the sense of being individualised enough for any one unique user or purpose [5]. The flexibility in application may also continue to be challenging for clinicians, who, in this phase, were responsible for introducing and supporting use of the client toolkit; a finding not dissimilar to other studies [30]. The collective action required to operationalise an intervention into practice may be simpler when it is tailored more specifically for a narrowly defined purpose or group of users.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, we acknowledge that this response may ultimately be inadequate and the flexibility, although clearly an ideal and desirable feature to fit a wide range of situations [14], may be difficult to balance with the sense of being individualised enough for any one unique user or purpose [5]. The flexibility in application may also continue to be challenging for clinicians, who, in this phase, were responsible for introducing and supporting use of the client toolkit; a finding not dissimilar to other studies [30]. The collective action required to operationalise an intervention into practice may be simpler when it is tailored more specifically for a narrowly defined purpose or group of users.…”
Section: Discussionmentioning
confidence: 86%
“…Consequently we were surprised to see these two divergent responses to the toolkit package. It may be that these responses highlight differing degrees of critical reflection [13,[28][29][30]. Alternatively, the concept of collective action highlights the work that clinicians have to do to integrate interventions into practice [20], which may have been limited.…”
Section: Discussionmentioning
confidence: 99%
“…The barriers to integrating self-management support to enable patients and families more control over their care are challenging in a highly routinised, medical environments such as acute major trauma. However, the benefits of multidisciplinary team (MDT) training in acute settings are emerging9 12 13 and evaluations have shown that clinicians trained to support self-management are more satisfied with their practice 14…”
Section: Problemmentioning
confidence: 99%
“…The Bridges SMP is an evidence-based educational intervention that has been tested and developed in different rehabilitation settings since 2008 13 17–20. Earlier work focused on implementation in community stroke settings but in 2013, Bridges SMP was successfully integrated into the working practices of a multidisciplinary acute stroke ward19 and in 2015 into a multidisciplinary traumatic brain injury pathway 13 21.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation